COVID‐19 and the pulmonary complications of sickle cell disease. Issue 2 (8th October 2020) - Sivalingam, Thivya; Inusa, Baba; Doyle, Pat; Oteng‐Ntim, Eugene
Abstract: Sickle cell disease (SCD) patients are commonly affected by pulmonary complications such as acute chest syndrome (ACS), pulmonary embolism (PE) and pneumonia that contribute to significant mortality risks. With a greater susceptibility to infection, they are deemed to be vulnerable patients during the current COVID‐19 pandemic. In emerging small case studies of SCD patients with COVID‐19 and further complicated by pneumonia, ACS, and/or PE, the clinical benefits of early exchange transfusion and Tocilizumab are evident. However, further clinical trials and larger cohort studies are essential to evaluate effective diagnostic and management options for this high‐risk group.